Effect of Milking Temperament on Milkability Traits and Milk Composition in Gir Cows - Agravat, Priyam H.; Patbandha, Tapas K.; Odedra, Mulraj D.; Savsani, Harish H.; Ahlawat, Anshu R.; Karangiya, Vijay K.; Kalasava, Shital K. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present research work was conducted on Gir cows (n=50) to study the association of temperament with milkability traits and milk composition. The temperament of Gir cows was assessed fortnightly using 4 point scale scoring system (1= docile, 2 = restless, 3 = nervous, 4 = aggressive). The milkability traits like milk let down time, milking time, milk yield and milk flow rate were recorded at fortnightly interval. Similarly, milk components like fat, solid not fat (SNF), protein, lactose and total solid (%) were estimated at fortnightly. The milk let down and milking time were significantly (p≤0.05) lower, while milk yield per milking and milk flow rate were significantly (p≤0.05) higher in docile cows as compared to restless, nervous and aggressive cows. All the milk constituents (fat, SNF, lactose, protein and total solid) were significantly (p≤0.05) higher in docile cows compared to other cows. Thus, it is concluded that Gir cows with docile temperament have better milkability, milk yield and milk quality.
Keywords: Gir cows; Milkability; Milk composition; Temperament